Isolation of streptococcus tigurinus - a novel member of streptococcus mitis group from a case of periodontitis - Dhotre, Shree V.; Mehetre, Gajanan T.; Dharne, Mahesh S.; Suryawanshi, Namdev M.; Nagoba, Basavraj S. (FEMS Microbiology Letters, 2014)
Streptococcus tigurinus is a new member of the Streptococcus viridians group and is closely related to Streptococcus mitis, Streptococcus pneumoniae, Streptococcus pseudopneumoniae, Streptococcus oralis, and Streptococcus infantis. The type strain AZ_3a(T) of S. tigurinus was originally isolated from a patient with infective endocarditis. Accurate identification of S. tigurinus is facilitated only by newer molecular methods like 16S rRNA gene analysis. During the course of study on bacteraemia and infective endocarditis with reference to periodontitis and viridians group of streptococci, a strain of S. tigurinus isolated from subgingival plaque of a patient with periodontitis identified by 16S rRNA gene analysis, which was originally identified as Streptococcus pluranimalium by Vitek 2. Confirmation by 16S rRNA gene analysis showed 99.39% similarity (1476/1485 bp) with S. tigurinus AZ_3a(T) (AORU01000002). To the best of our knowledge, this is the first report of isolation of S. tigurinus from the oral cavity of a periodontitis patient.
Keywords: periodontitis; Streptococcus tigurinus; VGS

Detection of clostridium tetani in human clinical samples using tetX specific primers targeting the neurotoxin - Ganesh, Madhu; Sheikh, Nasira K.; Shah, Pooja; Mehetre, Gajanan T.; Dharne, Mahesh S.; Nagoba, Basavraj S. (Journal of Infection and Public Health, 2016)
Tetanus resulting from ear injury remains an important health problem, particularly in the developing world. We report the successful detection of Clostridium tetani using tetX specific primers targeting the Cl. tetani neurotoxin. The sample was obtained from an ear discharge of a case of otogenic tetanus in a 2-year-old male child. Based on the culture results of the ear discharge, Gram staining and virulence testing by genotyping, a diagnosis of tetanus was confirmed. This is the first report from India on the successful detection of Cl. tetani in a human clinical sample using tetX specific primers targeting the Cl. tetani neurotoxin. (C) 2015 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Cl. tetani; Neurotoxin; Otogenic tetanus; Trismus

Molecular methods for identification of clostridium tetani by targeting neurotoxin - Dharne, Mahesh S.; Nagoba, Basavraj S.; Gohil, Kushal N. (Methods Molecular Biology, 2017)
Tetanus is a potentially fatal muscle spasm disease. It is an important public health problem, especially in rural/tribal areas of developing countries. Tetanus toxin, a neurotoxin (tetanospasmin ), is the most important virulence factor that plays a key role in the pathogenicity of tetanus . Confirmation of virulence by confirming the production of tetanospasmin by infecting species forms the most important part in the diagnosis of tetanus . Various molecular methods have been devised for confirmation of diagnosis by targeting different genes. The most common molecular methods are tetanospasmin producing (TetX) gene-targeted methods using TetX-specific primers. Here, we describe various molecular methods targeting TetX gene such as polymerase chain reaction, pulsed-field gel electrophoresis, Southern blotting, loop-mediated isothermal amplification assay, etc. to confirm the virulence of Cl. tetani.